Molecular defects in primary ciliary dyskinesia are associated with agenesis of the frontal and sphenoid paranasal sinuses and chronic rhinosinusitis - Schramm, Andre; Raidt, Johanna; Gross, Anika; Böhmer, Maik; Beule, Achim Georg; Omran, Heymut (Frontiers in Molecular Biosciences, 2023)
Background: Primary ciliary dyskinesia (PCD; MIM 242650) is a rare genetic disorder characterized by malfunction of the motile cilia resulting in reduced mucociliary clearance of the airways. Together with recurring infections of the lower respiratory tract, chronic rhinosinusitis (CRS) is a hallmark symptom of PCD. Data on genotype–phenotype correlations in the upper airways are scarce. Materials and methods: We investigated the prevalence, radiologic severity, and impact on health-related quality of life (HrQoL) of CRS in 58 individuals with genetically confirmed PCD. Subgroup analysis was performed according to the predicted ultrastructural phenotype based on genetic findings. Results: Among 58 individuals harboring pathogenic variants in 22 distinct genes associated with PCD, all were diagnosed with CRS, and 47% underwent sinus surgery. A total of 36 individuals answered a German-adapted version of the 20-item Sinonasal Outcome Test (SNOT-20-GAV) with a mean score of 35.8 ± 17, indicating a remarkably reduced HrQoL. Paranasal sinus imaging of 36 individuals showed moderate-to-severe opacification with an elevated Lund–Mackay Score (LMS) of 10.2 ± 4.4. Bilateral agenesis of frontal sinus (19%) and sphenoid sinus (9.5%) was a frequent finding in individuals aged 16 years or older. Subgroup analysis for predicted ultrastructural phenotypes did not identify differences in HrQoL, extent of sinus opacification, or frequency of aplastic paranasal sinuses. Conclusion: PCD is strongly associated with CRS. The high burden of disease is indicated by decreased HrQoL. Therefore, the upper airways of PCD individuals should be evaluated and managed by ear–nose–throat (ENT) specialists. Genetically determined PCD groups with predicted abnormal versus (near) normal ultrastructure did not differ in disease severity. Further studies are needed to gain evidence-based knowledge of the phenotype and management of upper airway manifestations in PCD. In addition, individuals with agenesis of the frontal and sphenoid paranasal sinuses and chronic respiratory symptoms should be considered for a diagnostic evaluation of PCD.